2014
DOI: 10.1113/jphysiol.2013.268680
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondria‐targeted antioxidant (MitoQ) ameliorates age‐related arterial endothelial dysfunction in mice

Abstract: Key pointsr The development of age-related arterial endothelial dysfunction, a key antecedent of increased cardiovascular disease (CVD) risk, is mediated largely by reduced nitric oxide bioavailability as a consequence of oxidative stress.r Mitochondria are critical signalling organelles in the vasculature, which, when dysregulated, become a source of excessive reactive oxygen species; the role of mitochondria-derived oxidative stress in age-related vascular dysfunction is unknown.r We show that a mitochondria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
188
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 206 publications
(204 citation statements)
references
References 60 publications
16
188
0
Order By: Relevance
“…Its acute (ex vivo) administration or chronic supplementation through the animals' drinking water completely restored carotid artery endothelium-dependent dilation in older mice by improving NO bioavailability. The improvements in endothelial function were associated with the normalization of age-related increases in total and mitochondria-derived arterial O 2 -production and oxidative stress (99). MitoQ has also been reported to prevent endotoxin-induced reductions in cardiac mitochondrial and contractile function in rodents (313).…”
Section: Skq1 Skqr1mentioning
confidence: 95%
See 1 more Smart Citation
“…Its acute (ex vivo) administration or chronic supplementation through the animals' drinking water completely restored carotid artery endothelium-dependent dilation in older mice by improving NO bioavailability. The improvements in endothelial function were associated with the normalization of age-related increases in total and mitochondria-derived arterial O 2 -production and oxidative stress (99). MitoQ has also been reported to prevent endotoxin-induced reductions in cardiac mitochondrial and contractile function in rodents (313).…”
Section: Skq1 Skqr1mentioning
confidence: 95%
“…Having confirmed the viability of the long-term exposure to mitochondria-targeted antioxidants, the following step is to assess whether the amount of accumulated compound is sufficient to act as an antioxidant in vivo. MitoQ has proved effective in several animal models of oxidative stress, such as various CVD settings, including endotoxin-induced cardiac dysfunction (313), age-related arterial endothelial dysfunction (99), cardiac ischemia/reperfusion (2), and doxorubicin-induced cardiac toxicity (40) and was shown to confer protection against an increase in blood pressure in rats that spontaneously develop hypertension (105). In one study, rats were administered 500 lM MitoQ for 2 weeks via their drinking water, after which their hearts were isolated and exposed to ischemia-reperfusion injury in a Langendorff perfusion system.…”
Section: Skq1 Skqr1mentioning
confidence: 99%
“…LPS [39,40] and rotenone [41,42] are well-known to induce systemic hemodynamic alterations. LPS may reduce interendothelial coupling and arteriolar conduction and cause hemodynamic effects [43].…”
Section: Aging and Disease • Volume 7 Number 3 June 2016 11mentioning
confidence: 99%
“…Graham et al [56] showed that MitoQ protects the development of hypertension, improves endothelial functions and reduces cardiac hypertrophy in young hypertensive rats. MitoQ is also a promising, novel strategy for preserving vascular endothelial function with advancing age and can prevent age-related CVD in mice [57] . However, MitoQ was not useful in protecting oxidative damage to cardiolipin, accumulation of protein carbonyls, activity of mitochondrial respiratory complexes, mtDNA copy number, or damage to mtDNA [58][59][60] .…”
Section: Future Perspectives Of Mitochondrial Pharmaceutics In Cardiomentioning
confidence: 99%